Case Studies of the Rise of Lesbian, Gay, Bisexual, and Transgender (LGBT) in Indonesian Society - Putri, Annisa Eka; Syam, Hidayani; Nazhifah, Nada; Azizah, Nikmah; Andesfi, Ratia (Lembaga Yasin AlSys, 2023)
Ith the opposite sex and that is considered unusual because it is not in accordance with the teachings of Islam and our Pancasila. LGBT are seen as people with mental disorders and need therapy. According to people who do, they feel that what they are doing is not wrong because there is encouragement from outside so they don't feel guilty, but for ordinary people, they think that it is wrong and very unusual. The factors that influence individuals to experience LGBT are the living environment where the environment has a huge influence on changes in a person's character and behavior that can lead us in a positive or negative direction. And in an environment, we should pay attention so that we don't fall into negative things like LGBT.